Assessment of socio-demographic and clinical factors associated with preeclampsia and eclampsia among primigravida attending tertiary care center in South India - Jaboi, Rency M.; S., Vahitha; ., Nivedita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The objective of the study was to identify the socio demographic and clinical factors associated with preeclampsia and eclampsia among primigravida attending a tertiary care center in South India. Methods: A quantitative research approach with case control design was used. Non-probability convenience sampling was used to select two groups of primigravida mothers i.e. one group with 108 mothers having preeclampsia or eclampsia and one group with 108 mothers not having preeclampsia or eclampsia. A structured questionnaire was employed to collect the data. Results: The study found that preeclampsia and eclampsia was significantly associated with maternal age (p=0.026), hemoglobin level (p=0.003), body mass index (p=0.001), weeks of gestation (p=0.016), age at menarche (p=0.003), age at first pregnancy (p=0.007), nutritional education (p=0.001), history of thyroid disorder (p=0.025), family history of hypertension (p=0.016), salt consumption (p=0.001), consumption of fried fatty food (p=0.008) and processed sugar (p=0.045), and intake of green leafy vegetables (p=0.001), pulses and beans(p=0.031) and activity (p=0.015). In the multiple regression analysis, body mass index (Adjusted Odds Ratio [OR] 2.28 [1.40-3.71] p=0.001), thyroid disorder (adjusted OR 2.756 [1.135-6.645] p=0.025) and intake of green leafy vegetables (adjusted OR 1.69 [1.223-2.360] p=0.002) were found to be independent risk factors associated with preeclampsia and eclampsia. Conclusion: The study concluded that the risk factors should be identified and evaluated during the antenatal visits for early detection so as to reduce maternal and neonatal mortality.